Business Ecosystem Profiling Visualization with Data Analytics: A Review - Joseph, Minnu Helen; Kärri, Timo (Complex systems informatics and modeling quarterly, 2025)
In business fields, an ecosystem, which is a shared environment consisting of organizations, individuals, resources, and technologies that are dynamically interconnected, is needed to provide and deliver emerging innovations and sustain competitive advantages. This article provides a thorough, systematic, and structured review of several frameworks of business ecosystems and their functioning. It also covers how data analytics can enhance ecosystem profiling by integrating it into these frameworks. Additionally, by considering advanced methodologies, this article highlights how actionable insights can be gained in the different operations and applications, from market analysis to risk management. Also, this review showcases several visualization tools that can be used to view complicated ecosystem structures, which helps employers to explore, analyze, and visualize data effectively. Finally, the article discusses the strengths and weaknesses of these tools and also offers some insights that can enhance decision-making in the emerging trends in the business ecosystem.